Teenagers' use of sexual health services: perceived need, knowledge and ability to access. Issue 4 (1st October 2004) - Parkes, Alison; Wight, Daniel; Henderson, Marion
Abstract : Introduction: An individual teenager's use of services may depend on perceived need, on knowledge of sexual health and local services, and on ability to access. This paper presents the first UK large-scale quantitative analysis of these factors, comparing those who use services with those who do not. Methods: 15/16-year-olds (n = 5747) were questioned about their use of sexual health services in the SHARE trial of a school sex education programme in 25 schools in Lothian and Tayside, Scotland, UK. Multilevel statistical models examined the role of different factors on service use. Results: One-third of teenagers had used a service, and use was strongly related to sexual experience. In addition, some family influences and being a school leaver were associated with service use, although we found no evidence for class, ethnic or religious barriers to use. Proximity to specialist clinics was linked with greater use, while low spending money and high parental monitoring were associated with less use. Teenagers with better knowledge, who rated their school sex education as effective, who were comfortable talking about sex and who had discussed contraception with peers were more likely to have used services. Differences in use relating to sexual experience, knowledge, feeling comfortable talking about sex and talking with peers helped to explain gender differences in service uptake. Conclusion: There is potential to influence service use through better knowledge and confidence imparted through school sex education, and by improving the links between services and schools.